Empowering School Initiatives : Memperkuat Sistem Keamanan dan Dukungan di SDN 1 Bogor - Mahanani, Fatma Kusuma; Amawidyati, Sukma Adi Galuh; Cahyaningtyas, Andarini Permata; Said, Noor; Firdaus, Aina Aulia; Ayu, Sandya Sarira; Almaira, Nur Fitria (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service aims to strengthen security and support to prevent and reduce the number of violence incidents in schools. The service was carried out with a group intervention method in the form of psychoeducation both training and non-training for the TPPK Task Force, teachers and staff, parents, and students of SDN 1 Cawas. The methods used were FGDs by developing regulations through School SMART GOALS; training psychoeducation to improve knowledge and skills and increase the self-efficacy of the TPPK Task Force; and non-training psychoeducation to increase knowledge and awareness of parents, teachers, and students regarding the prevention and handling of violence in schools. The results of the service showed an increase in knowledge, and self-efficacy of teachers and parents, as well as increased empathy and knowledge about understanding violence in schools and efforts to prevent violence. The psychoeducation activities were able to increase knowledge, skills, and awareness for all elements involved in the school, namely the TPPK Task Force, teachers, parents, and students at SDN 1 Cawas regarding the prevention and handling of violence in schools.